Innovation for creating a smart future - Sang M. Lee; Silvana Trimi (Journal of Innovation & Knowledge (JIK), 2018)
Today, we live in a dynamic and turbulent global community. The wave of mega-trends, including rapid change in globalization and technological advances, is creating new market forces. For any organization to survive and prosper in such an environment, innovation is imperative. However, innovation is no longer just for creating value to benefit individuals, organizations, or societies. The ultimate purpose of innovation should be much more far reaching, helping create a smart future where people can enjoy the best quality of life possible. Thus, innovation must search for intelligent solutions to tackle major social ills, seek more proactive approaches to predict the uncertain future, and pursue strategies to remove barriers to the smart future. This study explores the detailed requirements of a smart future, including both hardware types and soft social/cultural components.
Keywords: O; B; 650; Innovation classification; Value creation; Smart future; Well-being index